Isolating organic carbon fractions with varying turnover rates in temperate agricultural soils – A comprehensive method comparison. (October 2018) - Poeplau, Christopher; Don, Axel; Six, Johan; Kaiser, Michael; Benbi, Dinesh; Chenu, Claire; Cotrufo, M. Francesca; Derrien, Delphine; Gioacchini, Paola; Grand, Stephanie; Gregorich, Edward; Griepentrog, Marco; et al.
Abstract: Fractionation of soil organic carbon (SOC) is crucial for mechanistic understanding and modeling of soil organic matter decomposition and stabilization processes. It is often aimed at separating the bulk SOC into fractions with varying turnover rates, but a comprehensive comparison of methods to achieve this is lacking. In this study, a total of 20 different SOC fractionation methods were tested by participating laboratories for their suitability to isolate fractions with varying turnover rates, using agricultural soils from three experimental sites with vegetation change from C3 to C4 22–36 years ago. Enrichment of C4-derived carbon was traced and used as a proxy for turnover rates in the fractions. Methods that apply a combination of physical (density, size) and chemical (oxidation, extraction) fractionation were identified as most effective in separating SOC into fractions with distinct turnover rates. Coarse light SOC separated by density fractionation was the most C4-carbon enriched fraction, while oxidation-resistant SOC left after extraction with NaOCl was the least C4-carbon enriched fraction. Surprisingly, even after 36 years of C4 crop cultivation in a temperate climate, no method was able to isolate a fraction with more than 76% turnover, which challenges the link to the most active plant-derived carbon pools in models. Particles with density >2.8 g cm −3 showed similar C4-carbon enrichment as oxidation-resistant SOC, highlighting the importance of sesquioxides for SOC stabilization. The importance of clay and silt-sized particles (<50 μm) for SOC stabilization was also confirmed. Particle size fractionation significantly outperformed aggregate size fractionation, due to the fact that larger aggregates contain smaller aggregates and organic matter particles of various sizes with different turnover rates. An evaluation scheme comprising different criteria was used to identify the most suitable methods for isolating fractions with distinct turnover rates, and potential benefits and trade-offs associated with a specific choice. Our findings can be of great help to select the appropriate method(s) for fractionation of agricultural soils. Highlights: Combined physical and chemical fractionation was most successful. Dispersion and size separation is advisable to increase the range of turnover rates. Isolating more than five fractions inherits the risk of redundancy in turnover rates. Non-oxidizible and high density (>2.8 g cm- 3 ) fractions contained fewest young C. None of the methods isolated a fraction which entirely consisted of young C.